Potassium deficiency impairs photosynthetic induction via disrupted electron transport and photochemistry in Phaseolus vulgaris - Wu, Liling; Luo, Qi; Zhu, Ting; Wei, Yunmin (Frontiers in Plant Science, 2026)
Our previous study revealed that potassium (K) deficiency depressed carbon assimilation during photosynthetic induction in Phaseolus vulgaris. Building on this work, the current study presents a re-analysis of previously collected gas exchange and fluorescence measurements to further explore the contribution of electron transport and its components in regulating carbon assimilation under K deficiency, specifically examining electron transport rate (J), the fraction of open PSII reaction centers (qL), and non-photochemical quenching (NPQ). Our re-analysis revealed that plants supplied with deficient potassium demonstrated pronounced delay in electron transport activation, with c.430 s to achieve steady-state conditions compared to potassium sufficient plants (c. 215 s), which the delay was primarily attributed to slower qL increment and the sustained NPQ elevation. Normal K supplied plants maintained higher qL and J values throughout the induction, while NPQ levels eventually converged between treatments. Increased qL led to higher photosynthesis, highlighting qL as a key limiting factor in early photosynthesis induction. Taken together, under potassium deficiency, the delayed activation of electron transport reduces photosynthetic rates during induction, suggesting that improving qL could enhance photosynthesis under K-deficient conditions.